At Westonci.ca, we make it easy for you to get the answers you need from a community of knowledgeable individuals. Ask your questions and receive accurate answers from professionals with extensive experience in various fields on our platform. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.
Sagot :
Certainly! Let's go through each part step-by-step.
### Part a: Expand [tex]\((3x + 4)^2\)[/tex]
To expand [tex]\((3x + 4)^2\)[/tex], you can use the formula for the square of a binomial: [tex]\((a + b)^2 = a^2 + 2ab + b^2\)[/tex].
In this case, [tex]\(a = 3x\)[/tex] and [tex]\(b = 4\)[/tex].
So, we have:
[tex]\[ (3x + 4)^2 = (3x)^2 + 2 \cdot (3x) \cdot 4 + 4^2 \][/tex]
Now, calculate each term:
- [tex]\((3x)^2 = 9x^2\)[/tex]
- [tex]\(2 \cdot (3x) \cdot 4 = 2 \cdot 3 \cdot 4 \cdot x = 24x\)[/tex]
- [tex]\(4^2 = 16\)[/tex]
Putting it all together:
[tex]\[ (3x + 4)^2 = 9x^2 + 24x + 16 \][/tex]
### Part b: Expand [tex]\((2x + 4)(2x - 6)\)[/tex]
To expand [tex]\((2x + 4)(2x - 6)\)[/tex], you can use the distributive property (also known as the FOIL method for binomials).
[tex]\[ (2x + 4)(2x - 6) = 2x(2x) + 2x(-6) + 4(2x) + 4(-6) \][/tex]
Now, calculate each term:
- [tex]\(2x \cdot 2x = 4x^2\)[/tex]
- [tex]\(2x \cdot (-6) = -12x\)[/tex]
- [tex]\(4 \cdot 2x = 8x\)[/tex]
- [tex]\(4 \cdot (-6) = -24\)[/tex]
Now, combine like terms:
[tex]\[ (2x + 4)(2x - 6) = 4x^2 - 12x + 8x - 24 \][/tex]
Combining [tex]\(-12x\)[/tex] and [tex]\(8x\)[/tex]:
[tex]\[ 4x^2 - 12x + 8x - 24 = 4x^2 - 4x - 24 \][/tex]
### Final Answer:
a) [tex]\((3x + 4)^2 = 9x^2 + 24x + 16\)[/tex]
b) [tex]\((2x + 4)(2x - 6) = 4x^2 - 4x - 24\)[/tex]
### Part a: Expand [tex]\((3x + 4)^2\)[/tex]
To expand [tex]\((3x + 4)^2\)[/tex], you can use the formula for the square of a binomial: [tex]\((a + b)^2 = a^2 + 2ab + b^2\)[/tex].
In this case, [tex]\(a = 3x\)[/tex] and [tex]\(b = 4\)[/tex].
So, we have:
[tex]\[ (3x + 4)^2 = (3x)^2 + 2 \cdot (3x) \cdot 4 + 4^2 \][/tex]
Now, calculate each term:
- [tex]\((3x)^2 = 9x^2\)[/tex]
- [tex]\(2 \cdot (3x) \cdot 4 = 2 \cdot 3 \cdot 4 \cdot x = 24x\)[/tex]
- [tex]\(4^2 = 16\)[/tex]
Putting it all together:
[tex]\[ (3x + 4)^2 = 9x^2 + 24x + 16 \][/tex]
### Part b: Expand [tex]\((2x + 4)(2x - 6)\)[/tex]
To expand [tex]\((2x + 4)(2x - 6)\)[/tex], you can use the distributive property (also known as the FOIL method for binomials).
[tex]\[ (2x + 4)(2x - 6) = 2x(2x) + 2x(-6) + 4(2x) + 4(-6) \][/tex]
Now, calculate each term:
- [tex]\(2x \cdot 2x = 4x^2\)[/tex]
- [tex]\(2x \cdot (-6) = -12x\)[/tex]
- [tex]\(4 \cdot 2x = 8x\)[/tex]
- [tex]\(4 \cdot (-6) = -24\)[/tex]
Now, combine like terms:
[tex]\[ (2x + 4)(2x - 6) = 4x^2 - 12x + 8x - 24 \][/tex]
Combining [tex]\(-12x\)[/tex] and [tex]\(8x\)[/tex]:
[tex]\[ 4x^2 - 12x + 8x - 24 = 4x^2 - 4x - 24 \][/tex]
### Final Answer:
a) [tex]\((3x + 4)^2 = 9x^2 + 24x + 16\)[/tex]
b) [tex]\((2x + 4)(2x - 6) = 4x^2 - 4x - 24\)[/tex]
Thank you for choosing our service. We're dedicated to providing the best answers for all your questions. Visit us again. Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. Thank you for choosing Westonci.ca as your information source. We look forward to your next visit.